A QCM study of ORR-OER and an in situ study of a redox mediator in DMSO for Li–O2 batteries1. Issue 19 (21st May 2015) - Schaltin, Stijn; Vanhoutte, Gijs; Wu, Minxian; Bardé, Fanny; Fransaer, Jan
<x xml:space="preserve">Abstract</x> We present a detailed QCM-study of the ORR in DMSO. A redox mediator (TTF) allows almost complete reversibility during charging.